Surgical Dislocation of the Hip in the Treatment of Complex Osteochondral Injury to the Femoral Head. (August 2016) - Probe, Robert
Abstract : Purpose: The optimal treatment for osteochondral fracture of the femoral head associated with posterior dislocation remains unclear. A case can be made to treat small fragments and those that concentrically reduce nonoperatively. On the other end of the spectrum are those where significant size and residual displacement warrant consideration of operative fixation. This video demonstrates the treatment of a large complex multifragmentary osteochondral femoral head fracture with surgical dislocation. Methods: With the patient in lateral decubitus position, the trochanter is approached through lateral incision. The trochanter is cut and capsulotomy performed taking care to preserve the critical medial femoral circumflex artery. Fixation with headless screws is performed from the small comminuted fragments into the dominant section of intact femoral head. Results: Experience suggests that anatomic fixation through surgical dislocation can be carried out with low incidence of subsequent avascular necrosis and degenerative articular change. Given the degree of local osseous and muscular trauma, consideration should be given to prophylaxis of heterotopic bone. Discussion: Although small osteochondral fragments restricted to the acetabular fossa can be treated nonoperatively, the size and displacement of the presented fragment mandated operative reduction. Given the predicted complexity of repair, the surgical dislocation approach was chosen to provide maximum exposure optimizing the chances for successful fixation.